THE USE OF SUNDANESE LANGUAGE IN BANJARHARJO IN THE JAVANESE ETHNIC AREA - Sylvia Nurjannah; Bambang Yuniarto (CV. ADIBA AISHA AMIRA, 2025)
This research aims to examine the dynamics of Sundanese language usage in the Banjarharjo area, Brebes Regency, which is predominantly inhabited by the Javanese ethnic group. The focus of the study includes the history, origins of Sundanese language usage, differences between the Sundanese dialect of Banjarharjo and other regions, factors influencing Sundanese language usage, and its impact on the development of local culture. This research employs a qualitative approach with ethnographic methods. Data is collected through observation, in-depth interviews, and documentation involving local communities as primary informants. The research findings indicate that the use of the Sundanese language in Banjarharjo is rooted in the influence of the Padjajaran Kingdom and social interactions with the directly adjacent West Java region. The Sundanese language of Banjarharjo possesses its own distinctive characteristics, both in dialect, vocabulary, and intonation, which are influenced by the cultural acculturation of Javanese and Sundanese. Nevertheless, a shift in language usage is occurring among the younger generation, where the dominance of the Indonesian language is beginning to replace Sundanese as the primary means of communication.